The risk of imbalances in the financing of social protection in the context of demographic ageing - Cristina Boboc; Vergil Voineagu (Contemporary Economics, 2008)
In the next decades, developed countries will experience dramatic changes in their demographic trends. The retirement of the wide baby-boom generations, the increase in life expectancy and the decline in fertility ratios are likely to modify the size and the age-structure of their populations. The expected population ageing in European countries will burden the pension systems, especially wherever the pay-as-you-go pillar is predominant. Recently, migration has received a widespread attention as a solution to expected population decline and ageing in these countries. The flow of (young) migrants to developed countries is perceived as a means to alleviate the financial burden of pension systems. The aim of this contribution is to clarify the issue of aging on labour and capital markets in a macroeconomic perspective. A special attention is given to the risk of imbalances in the financing of social protection in the context of demographic ageing.
Keywords: 330